Enhancing spelling competence for English as a foreign language young learners through digital escape rooms - Saban, Marlene; Grünke, Matthias; Kahn-Horwitz, Janina (Frontiers in Education, 2024)
This study examines the efficacy of using a digital gamed platform in acquiring phoneme-grapheme correspondences of closed syllables with short vowels. Fifty-five fourth-grade English as a Foreign Language (EFL) learners navigated through five digital escape rooms where they learned, practiced, and produced target graphemes. Mixed methods analyses found that spelling competence in the intervention group as opposed to the control group improved in the post-test and continued to improve significantly in the delayed post-test. Following analysis of the participant interviews four themes emerged. Autonomous learning and self-monitoring were the dominant themes followed by engagement and motivation, self-confidence and self-esteem, and peer learning and social interaction in decreasing order of prevalence. Combining learning with play while participants navigated within the digital learning environment proved to be an effective method of teaching young EFL learners to spell. The results of this intervention contribute to recent research in the post-COVID-19 era and mirror OECD goals for the 21st century which have highlighted the need for effective digital platforms that promote independent learning while maximizing student engagement.